PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDNEGERI 005 SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Rully Rismadona Rully Rismadona; Zariul Antosa Zariul Antosa; Damanhur Daud Damanhur Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This observation was conducted by the IPS learning results which not achieve School KKM target score set by 65. On this case, observations are required to enhance learning process and raise student achievements for IPS Subject. The observation s is conducted to Class IV SD Negeri 005 Sedinginan Kec. Tanah Putih Kab. Rokan Hilir Period 2013/2014. By applied Cooperative teaching methods Type StudentTeams-Achievement Division(STAD) where first cycle conducted on February 28th, maret 7th,14th , 2014 and second cycle on Maret 21, Maret 28rd and 4 April th 2014. The observed student on Class IV SD Negeri 005 Sedinginan are 24 students, the Observation was observe Teacher’s activities, student’s activities and learning result orstudents achievement. Look up to observed students learning result, will show the average score achieved by students is increased. On average basis score 62,29 with classical completion 41,66% (incomplete). Increased on first cycle Average score is 70,20 with classical completion 62,5%(incomplete) and second cycle 84,16 with classical completion 91,66%(complete). The observation shown the relations of teacher and students activities to learning result, teacher activities on first cycle first meeting is 75% within good category. Second meeting is 83,3% within good category, by the second cycle first meeting is 83,3% within good category, and second meeting is 95,8% within very good category. The observation conclude that applying Cooperative type learning method type StudentTeams-Achievement Division(STAD) is able to enhance / increase learning achievement on Students Class IV SD Negeri 005 Sedinginan Kec. Tanah Putih Kab. Rokan Hilir Keyword: Cooperatif type STAD, social academic result